IMPLEMENTATION OF ACTIVE CHARCOAL FILTERING AND PHYTOREMEDIATION TOOLS AS AN EFFORT TO CONTROL MERCURY WASTE IN PADESA VILLAGE, LANTUNG DISTRICT - Agustikawati, Nurlaila; Adina Putri, Desy Fadilah; Ngurah Ketut Riyadi, Anak Agung; Hamdani, Hamdani; Setianingsih, Fitri (LPPM Univ. Ibn Khaldun Bogor, 2023)
Background: Land clearing disputes between communities and foreign investors for gold mining. Where in the end the community chose to open small-scale gold mining lands that only utilized spindles and mercury as amalgam with insufficient knowledge in the use of mercury and the processing of the resulting waste. Situation analysis: Residual mercury from the waste of each log averaged 0.03782 mg/L. The management of waste from logs containing mercury is not anti-absorbent and is left to dry on its own. Lack of concern for waste management is caused by a lack of knowledge about the dangers of mercury. The river water flow in Mitra Village comes from Tetanggga Village which has the same activities. Problems: The waste is allowed to dry on its own causing soil pollution, mercury levels in the river are 0.002 mg/L which exceeds the standard, and there is a lack of public knowledge about the dangers of mercury. Solution: Provide education through counseling on the impact of mercury, training on the manufacture and application of filtering tools and phytoremediation methods. Construction of permanent settling tanks and shelters so that they become anti-absorptive. Conclusion: As many as 94.4% had very good knowledge and 5.56% had good knowledge after conducting counseling on the impact of mercury and 2 logs which were being built with permanent anti-absorptive settling tanks and holding tanks.